2000
DOI: 10.1002/1097-0142(20000715)89:2<334::aid-cncr18>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of macrophage migration inhibitory factor predicts the prognosis of patients with adenocarcinoma of the lung

Abstract: BACKGROUND Macrophage migration inhibitory factor (MIF) is known to be a proinflammatory cytokine and glucocorticoid‐induced immunomodulator as well as a regulator of tumor growth. Although positive and negative effects of MIF on tumor cell growth have been reported, to the authors' knowledge the precise role of MIF in tumorigenesis remains unclear. In the current study the authors assessed expression of MIF protein and mRNA in lung adenocarcinomas with regard to patient prognosis. METHODS Immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 30 publications
3
63
2
1
Order By: Relevance
“…Of particular note is that NcMIF was clearly present in the nuclei. There were reports describing the localization of MIF in nuclei (Kamimura et al, 2000; Vedder et al, 2000), but these observations were not reported in later studies. NcMIF, as shown in the present study, as well as MIFs from other species does not contain a signal sequence or a nuclear localization signal (Arnoys and Wang, 2007), but the localization in the cytoplasm and nucleic as well as the extracellular compartments was apparent (Vedder et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Of particular note is that NcMIF was clearly present in the nuclei. There were reports describing the localization of MIF in nuclei (Kamimura et al, 2000; Vedder et al, 2000), but these observations were not reported in later studies. NcMIF, as shown in the present study, as well as MIFs from other species does not contain a signal sequence or a nuclear localization signal (Arnoys and Wang, 2007), but the localization in the cytoplasm and nucleic as well as the extracellular compartments was apparent (Vedder et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Among inflammatory mediators, pro-inflammatory cytokine MIF is a particularly interesting candidate. Indeed, MIF has been shown to have an important role in favouring tumorigenesis, and several research groups have shown a correlation between MIF and prognosis in hepatocellular carcinomas, gastric, ovarian, breast, colon, prostate, and non-small cell lung cancers (Meyer-Siegler et al , 1998; Kamimura et al , 2000; Tomiyasu et al , 2002; Legendre et al , 2003; Hira et al , 2005; Lue et al , 2007; Xia et al , 2009). The effect of MIF seems mediated via its binding to CD74 which expression is also linked with several forms of cancer (Datta et al , 2000; Meyer-Siegler et al , 2005, 2006; Binsky et al , 2007; McClelland et al , 2009; Nagata et al , 2009; Verjans et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its role in inflammation, many factors show that MIF has an important role in promoting tumorigenesis. Migration inhibitory factor is overexpressed in a variety of malignant tumours, such as breast (Lue et al , 2007), colon (Legendre et al , 2003), prostate cancers (Meyer-Siegler et al , 1998), and melanoma (Shimizu et al , 1999), glioblastoma multiform (Bacher et al , 2003) and lung adenocarcinomas (Kamimura et al , 2000; Tomiyasu et al , 2002). It increases tumour growth by favouring tumour cell proliferation and blocking apoptosis; after binding to CD74, it activates the PI3K/Akt pathway.…”
mentioning
confidence: 99%
“…In this regard, recent studies indicate that MIF protein levels are elevated in cancer patients [37], [38] and that MIF expression directly correlates with stage, metastatic spread, disease-free survival and tumor-associated neovascularization in e.g. lung, prostate, breast and gastric cancer, as well as glioma patients [37], [39], [40], [41], [42], [43]. Thus, loss of MIF in meningiomas with isolated monosomy 22/del(22q) may also play an important role in determining the more indolent behavior and the good prognosis of this subgroup of meningioma patients.…”
Section: Discussionmentioning
confidence: 99%